Detection of hidden defects of thermal protection of buildings and determination of some thermal properties of structural building materials by Non-destructive Thermal Imaging method - D. F. Karpov; M. V. Pavlov; A. G. Gudkov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The purpose of the work is the practical approbation of a nondestructive thermal imaging method to identify hidden (invisible) defects and qualitative analysis of the thermal protection of a complex of construction objects in the city of Vologda, as well as the study of some physical (thermophysical) indicators (coefficients of thermal conductivity, thermal resistance (thermal insulation) and heat transfer) of structural building material in the form of silicate brick.Method. The fundamental laws of the theory of heat transfer, thermal nondestructive testing, infrared and technical diagnostics, the current domestic regulatory and technical and regulatory documentation, field experiments on real objects and laboratory samples.Result. The results of the practical determination of hidden defects in the thermal shells of the complex of civil and industrial buildings functioning in the urban environment, thermophysical properties (coefficients of thermal conductivity, thermal resistance (thermal insulation), heat transfer) of modern building materials by methods of thermal non-destructive testing are presented. The locations of identified invisible defects of thermal protection of the surveyed construction objects are determined and recommendations for their elimination are proposed. The obtained values of thermophysical characteristics for the studied structural building material are consistent with the data of current regulatory documents.Conclusion. The features of the nondestructive method of infrared thermography in determining the hidden defects of the heatshielding shells of operated buildings of various functional purposes and the complex of thermophysical parameters of modern structural building materials are shown. The demand for thermal imaging during energy and technical surveys of construction objects, their individual structural elements, life support engineering systems, as well as studies on the refinement, quantification and prediction of various thermal properties of building materials and products has been experimentally confirmed.